EFFECT OF SERVICE LINE ON THE AVERAGE ENERGY CONSUMPTION OF WATER SUPPLY PUMPING STATION - Mahmood, Layth Abdulaleem; Al-Khashab, Hamid Adrees; Qassid, Anas Fakhry (Journal of Applied Engineering Science, 2024)
The pumps of high lift station consume a high magnitude of power to deliver the water supply to the community consumers, therefore it necessary to looking for means that help to reduce this consumption. The service pipe is an important part of water supply network but it is usually ignored in network analysis. The research focuses on the investigating the effects of this pipe on annual power consumption of pump station. The proposed model is constructed using EPAnet software and different values of diameter and C-coefficient are studied. Moreover, the effect of demand allocation is also studied. The results indicated that the increasing in diameter or in C-coefficient cause decreasing of annual power consumption. The application of demand allocation gives power consumption values less than that for no demand allocation application case. The statistical model showed the significance relationship among power consumption and service pipe properties, and showed that the effect of C-coefficient is higher than the effect of diameter.
Keywords: power consumption, pump, service pipe, water network